Garlic as an Antibacterial Against Isolates Resistant to Antibiotics Ciprofloxacin, Gentamicin, Tetracycline - Rahmaniar, Reina; Dyah Widhowati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The purpose of this study was to determine the effectiveness of crushed garlic at concentrations of 2%, 4%, and 6% against isolates of Staphylococcus aureus and Escherichia coli bacteria that have been tested for antibiotic sensitivity to Ciprofloxacin 5 µg, Gentamicin 10 µg, and Tetracycline 30 µg. The bacterial isolates were obtained from nasal mucosa samples from dogs and wound swabs from birds, chicken liver samples, chicken meat, chicken intestines, and beef. Isolates that were isolated and Identification of bacteria have confirmed phenotypically were then tested for sensitivity to antibiotics, ciprofloxacin 5 µg, gentamicin 10 µg, tetracycline 30 µg. Furthermore, the effectiveness of garlic as an antibacterial was tested using the disk diffusion method. Garlic was crushed and made at 2%, 4%, and 6% concentrations. The results obtained were presented in table form and presented descriptively. E. coli bacteria from chicken intestines are resistant to antibiotics ciprofloxacin 5 µg, gentamicin 10 µg, tetracycline 30 µg, while E. coli isolates from beef are still sensitive to antibiotics, ciprofloxacin 5 µg, gentamicin 10 µg, tetracycline 30 µg. S. aureus from bird wounds is resistant to gentamicin 10 µg, and isolates from dog nasal mucosa swabs are resistant to tetracycline 30 µg. Pureed garlic has good antibacterial activity at concentrations of 2%, 4%, and 6% against Gram-positive and Gram-negative bacterial isolates, both those that are resistant to antibiotics and isolates that are sensitive to antibiotics, ciprofloxacin 5 µg, gentamicin 10 µg, tetracycline 30 µg.